Analisis perbandingan manajemen strategi pada bank pembangunan daerah di Indonesia - Himmah, Nuzulia Faiqotul (Maliki Interdisciplinary Journal, 2023)
The performance of a bank can be assessed by analyzing its financial reports, while assessing the risks that may occur in a bank can be seen from strategic management and risk management. This research was carried out with the aim of knowing the performance of PPD DIY BPD DKI and Bank Jateng where there is strategic management, marketing management, risk management, business management, technology, services and products, as well as long-term strategic plans. The type of research used is a literature review with a quantitative approach. Namely annual data from 2022 where it is proven that the performance of BPD DIY is better than Bank Jateng and Bank DKI. To improve bank performance, they must carry out internal evaluations to minimize risk weaknesses